Testing Genuine Saving - Hamilton, Kirk (World Bank, Washington, DC, 2012)
The World Bank has been publishing estimates of adjusted net or "genuine" saving since 1999. This measure of saving treats depletion of natural resources as a type of economic depreciation. Hamilton uses recent theoretical results relating growth in saving to growth in future consumption to provide a test of genuine saving using historical data. Did measured genuine saving in 1976, for example, "predict" the observed changes in consumption over subsequent decades? The author tests four alternative measures of saving econometrically. The worst measure, in terms of explained variation, is traditional net saving. Genuine saving adjusted to reflect population growth exhibits the worst fit with theory. Both gross saving and genuine saving perform better, with good concordance with theory, while genuine saving exhibits a moderate advantage in terms of goodness of fit.